2022
DOI: 10.3390/cells11172621
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism and Regulation of Autophagy and Its Potential Role in Epilepsy

Abstract: Autophagy is an evolutionally conserved degradation mechanism for maintaining cell homeostasis whereby cytoplasmic components are wrapped in autophagosomes and subsequently delivered to lysosomes for degradation. This process requires the concerted actions of multiple autophagy-related proteins and accessory regulators. In neurons, autophagy is dynamically regulated in different compartments including soma, axons, and dendrites. It determines the turnover of selected materials in a spatiotemporal control manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 305 publications
0
16
0
Order By: Relevance
“…43 The dynamic regulation of autophagy across the different neuronal compartments in a spaciotemporal manner facilitates specialized neuronal functions. 44 In a study conducted in microglia, the cells were exposed to an acute drop from a high glucose state to a normal glucose state, and this was found to be accompanied by increased LC3BII expression. 45 The findings of this study indicated that increased metabolic stress can pave the way to neuroinflammation and neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…43 The dynamic regulation of autophagy across the different neuronal compartments in a spaciotemporal manner facilitates specialized neuronal functions. 44 In a study conducted in microglia, the cells were exposed to an acute drop from a high glucose state to a normal glucose state, and this was found to be accompanied by increased LC3BII expression. 45 The findings of this study indicated that increased metabolic stress can pave the way to neuroinflammation and neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an alteration of the proteins involved in the autophagy process could also be caused by other brain pathological conditions, such as epilepsy [48], ischemic and hemorrhagic stroke [49,50], Alzheimer's disease [51,52], and Parkinson's disease [53][54][55][56]. For example, a LC3-II increase and a LAMP2A decrease have been reported in the substantia nigra of Parkinson's disease models [53], as well as an alteration of GSK-3β and TDP-43 in some forms of dementia [52], and an impairment of LC3-II and p62 in epilepsy [48].…”
Section: Discussionmentioning
confidence: 99%
“…In a rat model of pilocarpine‐induced epilepsy, activation of the mTOR signaling pathway inhibits neuronal autophagy and avoids neuronal apoptosis, which can prevent acute epilepsy (Liu et al., 2022). Furthermore, autophagy dysfunction exists in epilepsy (Zhu et al., 2022), and the impairment of mTOR‐dependent autophagy has been found to be related to the mechanism by which mTOR overactivation promotes epilepsy (Limanaqi et al., 2020). Rapamycin induces early activation of the autophagy cascade via blockade of mTOR, while activation of mTOR inhibits the formation of autophagosomes (Crino, 2016).…”
Section: The Role Of the Mtor Signaling Pathway In Epilepsymentioning
confidence: 99%